2018
DOI: 10.1089/sur.2018.221
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation for the Management ofClostridium difficileInfection

Abstract: The clinical burden of Clostridium difficile infection (CDI) continues to grow. Despite the multitude of treatment options that have been developed and tested to combat the morbidity and death associated with CDI, recurrence remains common. As such, treatment modalities such as fecal microbiota transplantation (FMT) have become studied increasingly; FMT serves to transplant stool from carefully selected healthy subjects into C. difficile positive patients through a variety of delivery routes. In doing so, FMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
3
0
1
Order By: Relevance
“…[5] The study has shown that there is a higher recurrence rate of diarrhea within the control group compared to the fresh FMT group (24.6% vs. 11.0%, p = 0.05), which leads to the presumption that, despite the difficulty involved with its fresh FMT is more efficacious in preventing recurrent bouts of diarrhea associated with rCDI. Although frozen FMT has been known to decrease the number and frequency of donor screenings and expenses with application in healthcare settings [16] , the study could not detect a significant clinical difference with frozen FMT compared to its counterparts, including antibiotic treatment (p = 0.79) and capsule forms (p = 0.45). Although the ideal form of FMT remains unknown, one may still argue that both fresh and frozen FMT serve as beneficial alternatives to antimicrobial therapies in the prevention of recurrent bouts of CDI, especially following the initial clinical resolution of CDI with typical mainstays of treatment.…”
Section: Fresh Vs Frozen Fmtmentioning
confidence: 63%
“…[5] The study has shown that there is a higher recurrence rate of diarrhea within the control group compared to the fresh FMT group (24.6% vs. 11.0%, p = 0.05), which leads to the presumption that, despite the difficulty involved with its fresh FMT is more efficacious in preventing recurrent bouts of diarrhea associated with rCDI. Although frozen FMT has been known to decrease the number and frequency of donor screenings and expenses with application in healthcare settings [16] , the study could not detect a significant clinical difference with frozen FMT compared to its counterparts, including antibiotic treatment (p = 0.79) and capsule forms (p = 0.45). Although the ideal form of FMT remains unknown, one may still argue that both fresh and frozen FMT serve as beneficial alternatives to antimicrobial therapies in the prevention of recurrent bouts of CDI, especially following the initial clinical resolution of CDI with typical mainstays of treatment.…”
Section: Fresh Vs Frozen Fmtmentioning
confidence: 63%
“…There are many different methods to detect the three different targets: C. difficile toxin (EIA, cytotoxin), C. difficile (GDH, cytotoxin culture) and toxin B gene (PCR) [ 8 , 11 ]. In this case, we used several methods to detect the microbial isolate.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the deepening understanding of the pathogenesis of CDI in the medical community, great changes have been implemented in the management of CDI. Initially, metronidazole was mainly used as a first-line management[10]. Data before 2000 demonstrated that the proportion of patients receiving metronidazole to achieve a clinical cure was similar to the group of receiving vancomycin.…”
Section: Discussionmentioning
confidence: 99%